Manual descriptivo para la supervisión de contratos de conservación de carreteras - Calderón Alanís, Francisco Javier (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
In this work, it exposed in general his history of road maintenance in Mexico, what constitutes maintenance work and it reflects comprehensively the evolution and types of supervision External used for road maintenance Also illustrated is a document developed and defines the functions and duties of the supervisor before, during and after the development of the work and its limitations and responsibilities are established. The terms of reference for the work of the external oversight, which underwent a review and preliminary analysis, the result of the experience of the services performed specified. In addition, formats with their respective instructions for filling derived from the experience gained over the years of implementation of supervision of the works presented. Also in this document serve as a training and orientation for technical and professional staff of supervisory companies, which engineers and architects are supported in the exercise of their duties, referred to the lack of methods or literature define services for supervising road maintenance works. Therefore, it is expected to contribute to improving quality in exercising supervision, to streamline the proceedings in field, and make better roads practices.

En este trabajo se dan a conocer en forma general los antecedentes de la conservación de carreteras en México, en qué consisten los trabajos de conservación, se expone con amplitud la evolución y los tipos de la supervisión externa empleados para la Conservación de carreteras. Así mismo se elaboró un documento que ilustra, define las funciones y obligaciones del supervisor, antes, durante y después del desarrollo de la obra, además, se establecen sus limitaciones y sus responsabilidades. Se especifican los términos de referencia de los trabajos de la supervisión externa, los cuales fueron sometidos a una revisión y análisis previo, resultado de la experiencia de los servicios realizados, así como de la práctica del estado de arte. Además se presentan los formatos con sus respectivos instructivos de llenado derivado del conocimiento y experiencia obtenida del paso de los años de ejecución de la supervisión de las obras carreteras dentro de la SCT. Así mismo, este trabajo de tesis, se pretende sea una herramienta efectiva para la capacitación y orientación para el personal técnico y profesional de las empresas de supervisión, que se apoyen en el ejercicio de sus funciones.
Facultad de Ingeniería Civil. Maestría en Infraestructura del Transporte en la Rama de las Vías Terrestres
Keywords: info:eu-repo/classification/cti/7; FIC-M-2016-0938; Funciones; Términos; Formatos; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3115